National Urban Policy in the eyes of political scientist - Matyja, Rafał (Journal of Public Governance, 2015)
The article offers a critical review of the government document “National Urban Policy” (2014) from the viewpoint of political science. The author points out the fundamental f laws in the document related to the omission of important government actions inf luencing the development of cities, including changes in the administrative division of Poland, the establishment and closure of public institutions financed from the central budget, or restructuring of the economy. The article underlines a lack of consistency between the definition of cities as areas of concentration of economic activity and scientific institutions, and the proposed hierarchy of urban centres closely related to their administrative status (as regional capitals). The text also describes government attempts to impose certain policies in the area studied on local authorities where the latter should enjoy due autonomy (public participation, urban sprawl processes, transportation systems).